Training on making cendol starch using blue natural dyes extracted from telang flower essence - Shofi, Muh.; Putri, Mardiana Prasetyani (Journal of Community Service and Empowerment, 2020)
Telang flower, scientifically named Clitoria ternatea, is a wild plant that is commonly found in home yards and is usually treated as decorative flowers. This plant is a group of legumes. Its bright blue colour adds the beauty and bloom of the home yard. In addition to its attractiveness, telang flower has many benefits, they are for eye treatment, anti-depressant, heart health care, also circulation of lipoproteins in the body. Another, telang flower is also used as food or cake colouring. Therefore, it is important to educate public society about the use of telang flower as natural dyes in making cendol starch. The objective of this community service program is to improve public society’s knowledge on the use of telang flower as natural dyes in making cendol starch for society in Datengan Village Grogol District Kediri Regency. The program had been implemented on July 20 to August 30, 2019, located in Datengan Village Grogol District Kediri Regency. Results show that the partner community were very enthusiastic on the use of natural dyes from telang flower in making cendol starch. Based on the questionnaire distributed to the partner community, it reveals that there was a significant improvement on the partner community’s knowledge which reached 90% on the use of natural dyes in making cendol starch.